Cytokines in inflammatory bowel diseases – Update 2020. (August 2020) - Leppkes, M.; Neurath, M.F.
Abstract: Inflammatory Bowel Diseases (IBD), namely Crohn's Disease and Ulcerative Colitis, cause a significant disease burden in modern civilization. Ever since the introduction of anti-TNF-directed therapies 20 years ago, cytokines have attracted a lot of research attention and several cytokine-directed therapies have been implemented in the clinical treatment of these diseases. The research progress in these past years has underlined the importance of both myeloid and lymphoid elements of the immune system in the pathogenesis of IBD and their cytokine-mediated interplay. The conceptual framework of the mucosal cytokine network has shifted during these years from a T helper (Th) dichotomy (Th1/Th2) to the effector/regulatory T cell balance, while nowadays, the importance of myeloid cell instruction of lymphocytes, namely by IL-12 and IL-23, is increasingly recognized. Anti-IL-12p40 agents, like ustekinumab, groundbreakingly changed patient care, and anti-IL23p19-directed approaches are on the verge of grand success. In this review we present a modular approach to understand the cytokine network and put it into the context of the pathogenesis of IBD with a special focus on publications since 2014.